2011
DOI: 10.4293/108680811x13176785204193
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Appearance of Hem-O-Lok Clips in Patients Who Have Undergone Laparoscopic Nephrectomy or Nephroureterectomy

Abstract: Hem-O-Lok clips are radiopaque on computed tomography in patients who have undergone laparoscopic nephrectomy and nephroureterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…Variable reports about their CT-visibility exist [18,19]. Matsushita et al have shown that the density of hem-o-lok clip was 223 HU, consistent with its ex-vivo CT-based attenuation measurement [20]. In the current report, the density of the stone was 1609 HU and the stone analysis revealed calcium oxalate monohydrate, which explains the highly dense nature of the aggregate.…”
Section: Discussionsupporting
confidence: 77%
“…Variable reports about their CT-visibility exist [18,19]. Matsushita et al have shown that the density of hem-o-lok clip was 223 HU, consistent with its ex-vivo CT-based attenuation measurement [20]. In the current report, the density of the stone was 1609 HU and the stone analysis revealed calcium oxalate monohydrate, which explains the highly dense nature of the aggregate.…”
Section: Discussionsupporting
confidence: 77%
“…To date, the Hem‐o‐lok® clip is the most widely used vessel‐sealing device in children [4–6]. One of the issues is radiological opacity of the operative site due to foreign body reaction, which would bother the judgment of radiologists in late postoperative time [7]. Moreover, the Hem‐o‐lok® clip is undegradable, and its long‐term retention in the body brings risks such as tissue inflammation, local adhesion and chronic perforation of tissues and organs [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the Hem-o-lok clip is the most widely used vessel-sealing device in children [4][5][6]. The issue is radiological opacity of the operative site due to foreign body reaction, which would bother the judgment of radiologists in late postoperative time [7]. Moreover, the Hem-o-lok clip is undegradable, and its long-term retention in the body brings risks such as tissue in ammation, local adhesion, and chronic perforation of tissues and organs [8,9].…”
Section: Introductionmentioning
confidence: 99%